2014
DOI: 10.2106/jbjs.l.00856
|View full text |Cite
|
Sign up to set email alerts
|

3D CT Assessment of the Relationship Between Humeral Head Alignment and Glenoid Retroversion in Glenohumeral Osteoarthritis

Abstract: The importance of this study is that it presents quantitative data and clear guidelines to define two measurements of glenohumeral alignment as separate and important variables. The clinical relevance of these methods will be further defined when they are correlated with clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 25 publications
1
51
1
1
Order By: Relevance
“…More recently, subluxation was measured relative to the scapular axis, first in 2D [23], and lately in 3D [11,24]. Our 3D measurement method extended the classic 2D measurement proposed by Walch et al [10,23].…”
Section: Discussionmentioning
confidence: 90%
“…More recently, subluxation was measured relative to the scapular axis, first in 2D [23], and lately in 3D [11,24]. Our 3D measurement method extended the classic 2D measurement proposed by Walch et al [10,23].…”
Section: Discussionmentioning
confidence: 90%
“…18,21 The 3-dimensional (3D) measurement of the shoulder has been shown to improve the reliability of glenohumeral measurements as it seems to overcome these inherent positional errors of 2D CT scans. 1,8,12,15,16,20,22,25,26 Therefore, a 3D measuring method could improve the reliability of the posterior subluxation index measurement.…”
mentioning
confidence: 99%
“…The relationship between glenoid retroversion and HGA is less dependent on the amount of glenoid retroversion. Sabesan et al found no correlation between HGA and absolute glenoid version or the amount of bone loss in B2 glenoids, as these relationships are also likely impacted by the amount of posterior humeral head subluxation [6].…”
Section: Defined This Translation In Twomentioning
confidence: 99%
“…They described humeral glenoid alignment (HGA) as translation relative to the center of the glenoid fossa and humeral scapular alignment (HSA) as translation relative to the axis of the scapula [6] (Fig. 4).…”
Section: Defined This Translation In Twomentioning
confidence: 99%